Study of Wheat (Triticum aestivum L.) Seed Deterioration Pattern Using a Systems Approach - Enrico Syaefullah; Abdullah Bin Arif; Irpan Badrul Jamal; Rahmansyah Dermawan; Astuti Kurnianingsih; Marlin Sefrila; Miftakhul Bakhrir Rozaq Khamid; Isna Tustiyani; Elda Kristiani Paisey; Ubad Badrudin (Jurnal Agrivigor, 2025)
Wheat seeds, one of the orthodox seed types, naturally experience a decline in quality during long-term storage. This deterioration is a complex process that involves various factors throughout the seed's lifecycle. However, seed deterioration studies are based on static approaches. Therefore, moving from static to dynamic indicators, which describe changes in the state of seed biological systems over time, would be exciting. The study aimed to estimate the vigor and storability of wheat seeds based on a systems approach. The research was carried out using a systems approach, while the stages of the research were as follows: literature study and data collection from several scientific journals, preparation of flowcharts, models, simulations, and validation. The results showed that the estimation of wheat seed deterioration could be predicted through a systems approach. The estimation of wheat seed deterioration is a system that involves many variables that are interrelated and occur simultaneously. The following equations can estimate the wheat seed deterioration model: ROS(t) = ROS(t - dt) + (-H2O2) x dt; H2O2 = ROS x Changes index of H2O2; MDA = 4.62271 + (18.4012 - 4.62271) x exp (-22.2767 x H2O2 1.70613); FFA = 123.336 x exp (-10.1865 x H2O2); germination = 2.30234 + (109.524 - 2.30234) / (1 + exp (11.4657 x ln ('MDA' / 9.39342))). During storage, antioxidant enzymes that degrade reactive oxygen species (ROS) become inactive. The accumulation of ROS leads to membrane damage, resulting in decreased vigor, which is characterized by reduced germination rates.